Modificação superficial de polímeros via feixe de elétrons e plasma - Bozzo, Luíza Melchert (Universidade Federal de São Carlos, 2024)
Polymers have gained a significant foothold in the technology market due to their advantages over other materials such as steel, aluminum, and glass, particularly in terms of weight and cost. Additionally, they offer high versatility thanks to characteristics such as high mechanical and chemical resistance, ease of handling due to their flexibility, the possibility of adding additives, and recyclability. In this context, surface modification plays a crucial role in expanding the versatility of these materials and in the development of new technologies, as it allows new properties to be conferred to polymers without altering their bulk properties. In other words, it is possible to modify the polymer surface without the need to develop an entirely new material. In this way, surface modification techniques can enhance properties such as surface energy, wettability, and adhesion, thereby expanding the range of industrial applications. Among the surface modification techniques, plasma-based methods and irradiation with charged particle beams, particularly electrons, stand out. The first method offers advantages such as operational simplicity and low cost, with particular emphasis on the use of cold plasma. On the other hand, charged particle beam irradiation, although more complex, provides greater control over the reaction mechanisms involved, particularly when using low-energy beams (E < 20-30 eV), allowing modification of only the material’s surface.
Surface modification of polymers via electron beam and plasma
Keywords: Polímeros; Polymers; Modificação superficial; Surface modification; Feixe de elétrons; Electron beam; Plasma; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA